2016
DOI: 10.1186/s12985-016-0519-1
|View full text |Cite
|
Sign up to set email alerts
|

A robust model of natural hepatitis C infection using hepatocyte-like cells derived from human induced pluripotent stem cells as a long-term host

Abstract: BackgroundHepatitis C virus (HCV) could induce chronic liver diseases and hepatocellular carcinoma in human. The use of primary human hepatocyte as a viral host is restrained with the scarcity of tissue supply. A culture model restricted to HCV genotype 2a (JFH-1) has been established using Huh7-derived hepatocyte. Other genotypes including the wild-type virus could not propagate in Huh7, Huh7.5 and Huh7.5.1 cells.MethodsFunctional hepatocyte-like cells (HLCs) were developed from normal human iPS cells as a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…SEC14L2, an α -tocopherol transfer protein (Ttpa), was expressed in hepatocyte-like cells (HLCs), starting from human mesenchymal stem cells (hMSC) through induced pluripotent stem (iPS) cell reprogramming. Sa-Ngiamsuntorn et al indicated that, together with the expression of SEC14L2 and the addition of α -tocopherol, the expressions of inflammatory cytokines were upregulated during the infection that mimicked the inflammatory process [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…SEC14L2, an α -tocopherol transfer protein (Ttpa), was expressed in hepatocyte-like cells (HLCs), starting from human mesenchymal stem cells (hMSC) through induced pluripotent stem (iPS) cell reprogramming. Sa-Ngiamsuntorn et al indicated that, together with the expression of SEC14L2 and the addition of α -tocopherol, the expressions of inflammatory cytokines were upregulated during the infection that mimicked the inflammatory process [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The basis of this protocol was the spontaneous formation of cell aggregates (embryoid bodies) from pluripotent cells which has the capacity to give rise to all three germ layers [16]. To expand the hepatocytes, the most well-organized method is a monolayer culture of distinct cells in a step-wise manner exposure to specific cocktails of recombinant growth factors and cytokines, including Activin A, Wnt3a, HGF, OSM, FGF4, VEGF, EGF and BMP4 [184][185][186][187][188][189][190][191]. These approaches were designed to simulate the embryonic stages of hepatocyte lineage.…”
Section: Small Moleculementioning
confidence: 99%
“…Several groups have demonstrated that induced pluripotent stem cells–derived HLCs (iHLCs) express HCV and HBV entry receptors, and support productive viral infection with HCV or HBV particles, 41 , 47 , 48 , 49 Viral load in iHLCs is higher than in hepatoma cell lines, 47 and antiviral innate immune response is readily detectable on HCV or HBV infection, with increased expression of various type I interferon-stimulated genes similar to that observed in primary human hepatocytes in MPCCs. 39 , 41 Furthermore, infected iHLCs can be used for drug screening purposes because they respond to anti-HCV and -HBV drugs.…”
Section: Stem Cell–derived 2-dimensional Culture Systemsmentioning
confidence: 99%
“… 39 , 41 Furthermore, infected iHLCs can be used for drug screening purposes because they respond to anti-HCV and -HBV drugs. 39 , 41 , 47 …”
Section: Stem Cell–derived 2-dimensional Culture Systemsmentioning
confidence: 99%